What makes businesses commit to nature conservation? - Marlen S. Krause; Nils Droste; Bettina Matzdorf (Business Strategy and the Environment, 2020)
To halt the loss of biodiversity and ecosystem services, various actors including companies need to engage, but it is not yet clear what drives voluntary business commitments. We explore leverage points that might increase corporate action for conservation. We apply a structural equation model based on the theory of planned behaviour to analyse data from 618 German companies, collected through an online-survey in 2019. We show that a favourable attitude, driven by perceived business relevance and benefit prospects, fosters engagement. Perceived difficulties, such as lacking finances and knowledge, hinder the engagement. Customers, employees and the general public are presently the only stakeholder groups that drive corporate conservation engagement. Nevertheless, the expectation levels of virtually all stakeholders were found to be quite low and as such inadequate for the ecological crisis we face. We discuss how political will and goal setting can encourage more widespread business support for the natural environment.
Keywords: 330; biodiversity; corporate responsibility; ecosystem services; structural equation modelling; sustainable development; theory of planned behaviour